If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2k + 11 = 7 Reorder the terms: 11 + -2k = 7 Solving 11 + -2k = 7 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2k = 7 + -11 Combine like terms: 11 + -11 = 0 0 + -2k = 7 + -11 -2k = 7 + -11 Combine like terms: 7 + -11 = -4 -2k = -4 Divide each side by '-2'. k = 2 Simplifying k = 2
| 55x+.25=100 | | 28-19=3(y-6) | | (2x+1)(x+5)=3 | | 2t=-1 | | -11-x+5x=x-1-1 | | -95-9x=175+-6x | | 29-19=3(y-6) | | 2/5(9-2b)=-14 | | 8y+2=y-15 | | -9x+14=4x-12 | | -16y-20=-14y+40 | | 5(p)-14=8(p)+4 | | (7y-4)+(7x+9)=180 | | 3(x-2)+12=-6 | | 18x-14x+x-3x+3x=5 | | 4(x-4)+4-10x=30 | | 4(m)-4=4(m) | | -14=7(4-2u) | | -4-2x=6(-x+9) | | 3(k-5)=9 | | -8n-4=2+n-6-8n | | 4x+200=324 | | x^2+4x-544=0 | | 3x+29x-10=0 | | 3x+(-6)=-3 | | 4r+360=10d+6r | | -4p-4=-23 | | .66x+60=x | | -6x=45+3x | | 3x^2-34-24=0 | | 2x+6*5=2y | | 8(x)-2=-9+7(x) |